2017
DOI: 10.1039/c7ta00261k
|View full text |Cite
|
Sign up to set email alerts
|

Transparent wood containing CsxWO3nanoparticles for heat-shielding window applications

Abstract: A type of functionalized nanoparticles filled transparent wood composite for heat-shielding-window applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
172
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 27 publications
2
172
1
Order By: Relevance
“…[20] Briefly,t he wood templates were treated under the same delignification conditions for 18 hf irst, then the delignification templates were three-times vacuum-impregnated with prepolymerized MMA for 30 min to ensure that the templates were fully impregnated. The treated wood fibers were placed in ag lass mold to fabricate the transparent fiber wood by heating at 60 8Cf or 8h.P repolymerized at 80 8Cf or 15 min, the MMA monomer,w ith 0.3 wt %2 ,2'-azobis, was used as an initiator.T ot erminate the reaction, an ice-water bath was used to cool the prepolymerized MMA to room temperature.…”
Section: Fabrication Of Transparent Fiber Woodmentioning
confidence: 99%
See 2 more Smart Citations
“…[20] Briefly,t he wood templates were treated under the same delignification conditions for 18 hf irst, then the delignification templates were three-times vacuum-impregnated with prepolymerized MMA for 30 min to ensure that the templates were fully impregnated. The treated wood fibers were placed in ag lass mold to fabricate the transparent fiber wood by heating at 60 8Cf or 8h.P repolymerized at 80 8Cf or 15 min, the MMA monomer,w ith 0.3 wt %2 ,2'-azobis, was used as an initiator.T ot erminate the reaction, an ice-water bath was used to cool the prepolymerized MMA to room temperature.…”
Section: Fabrication Of Transparent Fiber Woodmentioning
confidence: 99%
“…[20] Thick or large-size transparent wood is highly desirable for practical applications.I np revious studies, however, the reported transparent wood samples were smalla nd of low thickness. [20] Thick or large-size transparent wood is highly desirable for practical applications.I np revious studies, however, the reported transparent wood samples were smalla nd of low thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially demonstrated by Fink in 1992 [3] for investigation of internal structure of wood species. However during recent years, the interest toward TW was significantly renewed in several research areas: material science designing multifunctional wood composites, [2,[4][5][6] energy saving technology focused on application of TW in solar cells, [7] and photonics dealing with light sources based on TW with additives. [8,9] Natural wood consists of three main components which have different refractive indices: cellulose (1.525 with light propagating www.advopticalmat.de through the material, haze is important to characterize scattering properties of medium in terms of image content.…”
Section: Introductionmentioning
confidence: 99%
“…For an enhancement of the pore volume present in these structures chemical delignification processes adapted from pulp and paper industry are a promising approach. Rather recently, this concept was applied with subsequent delignification and functionalization for the development of transparent wood [15,16,17]. …”
Section: Introductionmentioning
confidence: 99%